(untitled) (Global Journal of Science Frontier Research, 2024)
This paper suggests the possible existence of lepton color for charged leptons and neutral leptons as quarks possess Further lepton number conservation could be explained by lepton color scalar products More detailsare given to search for the relationship between the broken lepton number and PMNS And a speculation between broken lepton number and dark matter-energy